2010
DOI: 10.3109/08958370903524509
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary responses in spontaneously hypertensive and Wistar-Kyoto rats exposed to concentrated ambient particles from Detroit, Michigan

Abstract: Toxicological effects have been observed in rats exposed to concentrated ambient particles (CAPs) from different regions of the United States. The objective of this study was to evaluate the cardiopulmonary and systemic effects of CAPs in Detroit. The authors stationed a mobile concentrator at a location near major traffic and industrial sources. Spontaneously hypertensive (SH) and Wistar-Kyoto (WKY) rats were exposed to fine CAPs (diameter < 0.1-2.5 microm) 8 h/day for 13 consecutive days. Animals were implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
3
9
1
Order By: Relevance
“…Specifically, we were able to link factors of motor vehicles and local emission sources unique to southwest Detroit to altered HR and HRV. These findings agree with our recent studies using less robust exposure metrics, which found that local emissions sources upwind of the exposure site, including incinerators, refineries, and metal processing operations, were linked to cardiopulmonary effects, including pulmonary deposition of metals (Morishita et al 2006; Rohr et al 2010). With the exception of one association we found for a coal/secondary sulfate factor in the winter, the present study also shows that similar local sources, including cement/lime production, sludge incineration, refineries, iron/steel, and motor vehicles influence HRV metrics.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Specifically, we were able to link factors of motor vehicles and local emission sources unique to southwest Detroit to altered HR and HRV. These findings agree with our recent studies using less robust exposure metrics, which found that local emissions sources upwind of the exposure site, including incinerators, refineries, and metal processing operations, were linked to cardiopulmonary effects, including pulmonary deposition of metals (Morishita et al 2006; Rohr et al 2010). With the exception of one association we found for a coal/secondary sulfate factor in the winter, the present study also shows that similar local sources, including cement/lime production, sludge incineration, refineries, iron/steel, and motor vehicles influence HRV metrics.…”
Section: Discussionsupporting
confidence: 92%
“…In a similar but limited study at the same location using half as many subjects (Rohr et al 2010), we attempted to make comparisons with CAP composition using 8-hr integrated samples. Although we detected exposure-related differences in the lung, we failed to find significant changes in cardiac function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also some suggestive evidence that animal models of certain human diseases have different CRP responses to PM exposure. Significantly stronger PM-induced CRP responses were observed in spontaneously hypertensive rats, compared with rats with normal blood pressure (32, 33). In another study, serum CRP levels increased significantly in nondiabetic rats after PM 2.5 exposure, but increase of CRP levels in diabetic rats did not reach statistical significance (35).…”
Section: Introductionmentioning
confidence: 97%